The incidence and prevalence of delirium across palliative care settings: A systematic review. (September 2019) - Watt, Christine L; Momoli, Franco; Ansari, Mohammed T; Sikora, Lindsey; Bush, Shirley H; Hosie, Annmarie; Kabir, Monisha; Rosenberg, Erin; Kanji, Salmaan; Lawlor, Peter G
Background: Delirium is a common and distressing neurocognitive condition that frequently affects patients in palliative care settings and is often underdiagnosed. Aim: Expanding on a 2013 review, this systematic review examines the incidence and prevalence of delirium across all palliative care settings. Design: This systematic review and meta-analyses were prospectively registered with PROSPERO and included a risk of bias assessment. Data sources: Five electronic databases were examined for primary research studies published between 1980 and 2018. Studies on adult, non-intensive care and non-postoperative populations, either receiving or eligible to receive palliative care, underwent dual reviewer screening and data extraction. Studies using standardized delirium diagnostic criteria or valid assessment tools were included. Results: Following initial screening of 2596 records, and full-text screening of 153 papers, 42 studies were included. Patient populations diagnosed with predominantly cancer ( n = 34) and mixed diagnoses ( n = 8) were represented. Delirium point prevalence estimates were 4%–12% in the community, 9%–57% across hospital palliative care consultative services, and 6%–74% in inpatient palliative care units. The prevalence of delirium prior to death across all palliative care settings ( n = 8) was 42%–88%. Pooled point prevalence on admission to inpatient palliative care units was 35% (confidence interval = 0.29–0.40, n = 14). Only one study had an overall low risk of bias. Varying delirium screening and diagnostic practices were used. Conclusion: Delirium is prevalent across all palliative care settings, with one-third of patients delirious at the time of admission to inpatient palliative care. Study heterogeneity limits meta-analyses and highlights the future need for rigorous studies.